(untitled) (Baltic Journal of Sport and Health Sciences, 2012)
Research background and hypothesis. Nutrition therapy is important for the prophylaxis of diabetes, managing existing diabetes, and preventing or at least slowing the rate of development of diabetes complications. We suppose that nutrition peculiarities and addictions of young diabetic women interplay with their body composition. Research aim was to determine nutrition peculiarities and addictions of young girls with diabetes mellitus type 1 and healthy persons aged 18–25 years and their interplay with body composition. Research methods. The study included 24 healthy young women (mean age: 20.2 ± 1.2), and 14 young women with type 1 diabetes (mean age: 21.9 ± 0.8). Anthropometric measurements were performed, and a questionnaire to determine nutrition peculiarities and addictions was used. Research results. The values of BMI, waist circumference, waist to hip ratio index were statistically significantly higher in women with type 1 diabetes (p < 0.05). Vegetable oil for cooking was reported by 86% of diabetic and 58% of healthy women (p < 0.05). 50% of diabetics responded that they always had their meals at regular hours, and only 4% of healthy women pointed out irregular hours of their meals (p < 0.05). Evaluations of addictions did not reveal any significant difference (p > 0.05). Nutrition peculiarities and addictions did not have any effect on the body composition of the research participants. Discussion and conclusions. BMI was within normal limits, however, this indicator was significantly higher in women with type 1 diabetes. Waist circumference and waist to hip ratio were also significantly higher in women with type 1 diabetes mellitus. Young diabetic women reported having meals at regular hours more often. Vegetable oil for cooking was used in both groups; additionally, healthy women were more likely to consume home-grown foods. When evaluating addictions, a significant difference between groups was not observed. Nutrition peculiarities and addictions did not have any effect on body composition. Keywords: anthropometrical data, questionnaire, smoking, alcohol.